Correction of Received Power for Doppler Measurements by FMICW Radars - Rejfek, Luboš; Fišer, Ondřej; Matoušek, David; Beran, Ladislav; Chmelař, Pavel (Croatian Society Electronics in Marine - ELMAR, 2017)
This electronic document is aimed at the corrections of the received power through frequency modulated interrupted continuous wave radars. These corrections are important for the correct interpretation of the target characteristics. Power corrections, described in this paper, are modified for the measurement of the Doppler shifts. Doppler shifts are calculated by the using of the two dimensional fast Fourier transform. In practical part of this paper four types of windows were compared during calculation of the two dimensional spectra. We concluded that the correction coefficients should be determined for each window individually.
Korekce přijatého výkonu pro Dopplerovská měření pomocí FMICW radaru
Keywords: FMICW radar; Spectral analysis; Doppler measurements; Power corrections; Target reflectivity